53BP1 expression as a biomarker to differentiate thyroid follicular tumors. Issue 3 (March 2021) - Sato, Ayako; Matsuda, Katsuya; Motoyama, Takahiro; Mussazhanova, Zhanna; Otsubo, Ryota; Kondo, Hisayoshi; Akazawa, Yuko; Higuchi, Miyoko; Suzuki, Ayana; Hirokawa, Mitsuyoshi; Miyauchi, Akira; Nagayasu, Takeshi; et al.
Abstract : We have previously reported that the expression of p53-binding protein 1 (53BP1) in nuclear foci (NF), a marker reflecting DNA damage response (DDR), detected using immunofluorescence (IF) is useful to estimate the malignant potency of diverse cancers. In this prospective study, we clarified the impact of 53BP1 expression via IF as a biomarker to differentiate thyroid follicular tumors (FTs) with liquid-based cytology (LBC). A total of 183 consecutively obtained-LBC samples, which were preoperatively suspected as FTs, were analyzed. Before histological diagnosis, the type of 53BP1 immunoreactivity in LBC was classified as follows: low DDR type, one or two NF; high DDR type, three or more NF; large foci type, larger than 1.0 μm; abnormal type, intense nuclear staining. Among the 183 cases, 136 cases were postoperatively diagnosed as FTs, including adenomatous goiter (AG, n = 30), follicular adenoma (FA, n = 60), FT-uncertain malignant potency (FT-UMP, n = 18), and follicular carcinoma (FC, n = 28), and 47 cases were diagnosed as tumors other than FTs or technically inadequate materials. Total 136 FT cases were collated with the type of 53BP1 immunoreactivity in LBC. The mean incidence expressing abnormal 53BP1 expression was significantly higher in FC than FA (9.5% vs 2.6%, P -value < 0.001). When adopting 4.3% as a cut-off value to distinguish FC from FA, the sensitivity, specificity, positive predictive value, and negative predictive value were 89.3, 83.3, 71.4, and 94.3%, respectively. Therefore, IF analysis of 53BP1 expression can be employed as a novel technique to diagnose FTs and to distinguish between different types of FTs using LBC.